Sources de la transmission manuscrite en Islam : livres, écrits, images
1 online resource.
Keywords: The Festschrift Sources de la transmission manuscrite en Islam brings together a set of contributions at the forefront of research on the theme of the manuscript book, writing and image in Islam, from all periods.Les mélanges Sources de la transmission manuscrite en Islam réunissent un ensemble de contributions à la pointe de la recherche sur le thème du livre manuscrit, de l’écrit et de l’image en Islam, toutes périodes confondues. Sources de la transmission manuscrite en Islam : livres, écrits, images is a Festschrift offered to Marie-Geneviève Guesdon, curator of Arabic manuscripts at the BNF, codicologist and specialist in Arabic manuscript books, on the occasion of her retirement. It brings together fourteen original contributions for which the collections of the BNF provided an essential source. Handwritten transmission in Islam over the long period is the central axis of the volume. New hypotheses are emerging, both on questions of transmission by shaykhs or scribe-painters and the circulation of ideas, texts and knowledge, as well as on the status and attribution of writings, the making of books, and the history of libraries. Sources de la transmission manuscrite en Islam : livres, écrits, images sont des mélanges offerts à Marie-Geneviève Guesdon, conservatrice des manuscrits arabes à la BNF, codicologue et spécialiste du livre manuscrit arabe, à l’occasion de son départ à la retraite. Il réunit quatorze contributions originales dont les collections de la BnF forment une source essentielle. La transmission écrite en Islam sur la longue période est l’axe central du volume. De nouvelles hypothèses emergent, aussi bien sur les questions de transmission par les shaykhs ou les scribes-peintres, de circulation des idées, des textes et des savoirs que de statut et d’attribution des écrits, de fabrication du livre et d’histoire des bibliothèques. Avec: Annie Berthier, Zouhour Chaabane, Khalid Chakor-Alami, François Déroche, Alain J. Desreumaux, Anne-Marie Eddé, Abdelouahad Jahdani, Khaled Kchir, Françoise Micheau, Anne Regourd, Francis Richard, Muriel Roiland, Jacqueline Sublet, Tal Tamari, Saadou Traoré, Annie Vernay-Nouri Annie Berthier, Zouhour Chaabane, Khalid Chakor-Alami, François Déroche, Alain J. Desreumaux, Anne-Marie Eddé, Abdelouahad Jahdani, Khaled Kchir, Françoise Micheau, Anne Regourd, Francis Richard, Muriel Roiland, Jacqueline Sublet, Tal Tamari, Saadou Traoré, Annie Vernay-Nouri.